1995
DOI: 10.1006/viro.1995.0047
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Treatment Inhibits Virus Replication in HIV-1- and SIV-Infected CD4+ T-Cell Lines by Distinct Mechanisms: Evidence for Decreased Stability and Aberrant Processing of HIV-1 Proteins

Abstract: We have examined the effects of interferon (IFN)-alpha/beta on HIV-1 and SIV replication in CD4+ T-cell lines. To enable us to examine these effects on a single cycle of virus replication, cells were synchronously infected with HIV-1 LAI or SIV mac251. Cell lines included MT4 cells which were responsive to IFN and, as controls, C8166 cells which failed to respond to interferon treatment. Similar to previous reports, we found that replication of both HIV-1 and SIV was markedly inhibited in responsive MT4 cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 0 publications
3
26
0
Order By: Relevance
“…Consequently, the virions used in our assays were from apparently healthy H9 cultures. Under other conditions, including more prolonged infections, nonpermissive cells can exhibit cytopathic changes or produce cytokines, interferons, or stress responses that could secondarily perturb synthesis or processing of virion components (1). In addition, our results support other evidence that vif deletion HIV-1 released by nonpermissive human cells becomes blocked at a postpenetration step of infection in target cells (39).…”
Section: Discussionsupporting
confidence: 80%
“…Consequently, the virions used in our assays were from apparently healthy H9 cultures. Under other conditions, including more prolonged infections, nonpermissive cells can exhibit cytopathic changes or produce cytokines, interferons, or stress responses that could secondarily perturb synthesis or processing of virion components (1). In addition, our results support other evidence that vif deletion HIV-1 released by nonpermissive human cells becomes blocked at a postpenetration step of infection in target cells (39).…”
Section: Discussionsupporting
confidence: 80%
“…4c), because this type I interferon plays a key role in initiating innate antiviral responses and limiting HIV-1 replication (Francis et al, 1992;Agy et al, 1995;Taylor et al, 1998;Collado-Hidalgo et al, 2006). Indeed, recent studies suggest that ␤-adrenergic inhibition of IFNB response plays a central role in the ability of catecholamines to upregulate HIV-1 replication (Collado-Hidalgo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Type I interferons (IFN-␤ and 23 IFN-␣ family members) are well documented suppressors of HIV-1 and SIV replication, and are believed to be major physiological determinants of lentiviral replication rates (Francis et al, 1992;Agy et al, 1995;Taylor et al, 1998;Collado-Hidalgo et al, 2006). Experimental induction of IFN-␤ has been shown to suppress SIV replication in vivo (Matheux et al, 2000), and our previous work has shown that NE-induced impairment of type I interferon expression represents a major mechanism by which NE enhances HIV-1 replication in vitro (Cole et al, 1998;Collado-Hidalgo et al, 2006).…”
Section: Role Of Type I Interferonsmentioning
confidence: 99%
“…Type I IFN inhibit HIV replication in some T-cell lines (2,28,40,60,67,71). To identify a convenient model in which we could follow the effect of IFN on HIV replication, we infected four cell lines commonly used in HIV studies, Jurkat, CEM, HUT-78, and MT4R5, in the presence of IFN-␣ or -␤.…”
Section: Inhibition Of Hiv Replication By Type I Ifn In Primary Tmentioning
confidence: 99%
“…IFN treatment of primary T lymphocytes, macrophages, and some T-cell lines efficiently inhibits early phases of infection, including HIVinduced cell fusion and reverse transcription (15,16,26,27,46,60,61,70). IFN also impair later steps of the HIV replication cycle, ranging from reduced virus protein processing and stability to altered virion release and composition (2,8,17,19,20,23,26,28,39,49,63,71,72). In these early reports, the experimental systems were optimized to measure the effect of IFN on either early or late steps of the virus replication cycle but did not fully explore the long-term efficacy of IFN.…”
mentioning
confidence: 99%